PENGARUH PENAMBAHAN CONTRACT RELAX PADA INTERVENSI TENS DAN MC. KENZIE EXERCISE PADA PERUBAHAN DERAJAT SLR PENDERITA ISCHIALGIA DI RSUD SALEWANGANG MAROS - Aco Tang; Andi Halimah; Sudaryanto Sudaryanto; Hasbiah Hasbiah (Politeknik Kesehatan Makassar, 2020)
Ischialgia is a manifestation of low back pain caused by clamping of the ischiadicus nerves. Ischialgia is pain that radiates down along the course of the ischiadicus nerve root which causes a change in the degree of SLR.This research is a quasi-experimental study with a pre test-post test control design study which aims to determine the effectiveness of adding Contract Relax to the TENS and Mc interventions. Kenzie compared to TENS and Mc. Kenzie alone on changes in SLR degrees of Ischialgia sufferers. This research was conducted at Salewangang Maros Hospital, with a sample of ischialgia sufferers who fit the researcher's inclusion criteria so that a total sample of 12 people was obtained. The number of samples was divided into 2 groups, namely the treatment group of 6 people who were given Contract Relax, TENS, and Mc. Kenzie and the control group as many as 6 people were given TENS, and Mc. kenzie.The results of the paired sample t test in the treatment group obtained a value of p = 0.000 <0.05, which means that the administration of Contract Relax, TENS, and Mc. Kenzie can produce a significant increase in the degree of SLR in patients with ischialgia, whereas in the control group a value of p = 0.000 <0.05 is obtained, which means that the administration of TENS and Mc. Kenzie can make a significant improvement in SLR degrees. Then based on the results of the independent sample t test, the value of p = 0.016 <0.05 was obtained, which means that the addition of Contract Relax to the TENS and Mc interventions. Kenzie is more effective than TENS and Mc. Kenzie alone on increasing the degree of SLR in patients with ischialgia.Thus the addition of Contract Relax to the TENS and Mc interventions. Kenzie is more effective than TENS and Mc. Kenzie alone on increasing the degree of SLR in patients with Ischialgia.Keywords: Contract Relax, TENS, Mc.Kenzie, Ischialgia, SLR Degree.